About the Emphasis on Self-Expression and Other Consequences of Identifying Democracy with Capitalism. A Critical Sketch - Hudzik, Jan P. (Sensus Historiae, 2022)
The focus of this paper is the question of democracy: what is it in the conditions of the world governed by neoliberal ideology and the related high growth economy, where power elites are closely related to business elites, and the state is treated as a place to allocate private capital? Where is the common good in all this? The author contrasts political science, focused on quantitative research that aims at discovering the laws of democratic development, with a critical democratic theory. The text consists of five basic parts. The first one presents briefly the assumptions of the theory of Ronald Ingelhart and Christian Welzel, according to which economic development leads to a growing emphasis on self-expression values. Parts two and three analyze the effects of the consolidation of democracy and liberal capital - the phenomena described by notions such as post-democracy, illiberal democracy or deep state. Parts four and five present a certain model of critical political theory, which refers to the opaque social reality and relational political identities, criticizes the system, but also helps the weaker and the injured, enabling them to get out of critical situations. The universal truth, as a just truth, becomes available to such a theory only when the world experienced simultaneously by people and their researcher finds itself in a state of crisis.